PENGARUH MEDIA PERMAINAN SIDEWALK MAZE TERHADAP KEMAMPUAN MOTORIK KASAR ANAK USIA 5-6 TAHUN DI TAMAN KANAK-KANAK - Muhammad Yusri Bachtiar; Siti Khadijah Alam; Azizah Amal; Fitriani Dzulfadhilah (Lembaga Penerbitan dan Publikasi Ilmiah (LPPI) Universitas Muhamamdiyah Palopo, 2024)
This study aims to determine the effect of the sidewalk maze game media on the gross motor skills of children aged 5-6 years in kindergartens in Barru district. The research approach used is a quantitative approach with a Quasi Experimental Design research type. The population in this study was 172 children. Sampling in this research used the Purposive Sampling technique. The sample consisted of 62 children, 31 children in the experimental group and 31 children in the control group. The data analysis techniques used are descriptive statistical analysis and parametric statistical analysis using normality tests, homogeneity tests and hypothesis tests. The results of the data analysis obtained were Asym (2-tailed) = 0.000 < 0.05, meaning that H1 was accepted and H0 was rejected. Thus, the gross motor skills in the experimental group were better than the control group, this proves that the use of sidewalk maze game media has a significant influence on the gross motor skills of children aged 5-6 years in the Barru Regency Kindergarten..